Geography textbooks and the reproduction of a racist and ethnocentric world view among young people in Flanders - Nick Schuermans (Belgeo)
The final attainment levels of Flemish secondary geography education stress the importance of respect for other societies and the specific way of life of other people. As a consequence, curricula focus more than ever on topics such as the global north-south divide, migrations and the multicultural city. Drawing on an analysis of fifty Flemish geography textbooks published between 1896 and 2004, this paper critically addresses the way in which these topics have been presented. The study reveals that an emphasis on racial differences has been largely replaced by a focus on cultural differences. Yet, because of the strong emphasis on cultural otherness, the one-sided explanation of cultural conflicts, the manifest silencing of discrimination and xenophobia and the use of an exclusionary us-them-perspective, the textbooks (re)produce a racist and ethnocentric world view among young people in Flanders. Hence, the article concludes with four propositions for geography textbooks which motivate students to become part of a more inclusive, more diverse and more just society.